The Erosional and Depositional Potential of Holocene Tibetan Megafloods Through the Yarlung Tsangpo Gorge, Eastern Himalaya: Insights From 2D Hydraulic Simulations. Issue 5 (23rd May 2022) - Morey, Susannah M.; Huntington, Katharine W.; Turzewski, Michael D.; Mangipudi, Mahathi; Montgomery, David R.
Abstract: Profound effects of episodic megafloods (≥10 6  m 3 /s) have been observed on Earth and Mars. Quaternary megafloods sourced from valley‐blocking glaciers on the Tibetan Plateau likely play an important role in the geomorphic evolution of the Yarlung‐Tsangpo Gorge and mountain landscape of the eastern Himalaya. We use the first 2D numerical simulation of a megaflood sourced from a reconstructed 81 km 3 Tibetan lake to analyze flood hydraulics and examine the erosional and depositional potential of megafloods in mountain landscapes. The simulated flood has a duration >60 hr and a peak discharge of 3.1 × 10 6  m 3 /s. We find that the extent of inundated features like terraces, narrow valley sections, tight meander bends, and overtopped ridges influences locations of observed maximum depth (370 m), speed (76 m/s), and bed shear stress (>100 kPa), creating dynamic patterns of erosive potential. Consequently, it is difficult to predict local (≤1 km) patterns of megaflood erosional potential from either unit stream power or flood power from smaller magnitude outburst floods. However, both are useful when predicting regional (≥25 km) order‐of‐magnitude shifts in megaflood flood power. Portions of the flood domain downstream of the Gorge experience lower bed shear stresses and flood power <5 kW/m 2, indicating potential for significant deposition. We suggest widespread deposition of boulders within the modern channel and fine‐grained particles on hillslopes during a megaflood likely impedes subsequent erosion and affects channel width and longitudinal form throughout the flood pathway. Our findings show the legacy of megaflooding in mountainous terrain includes both extensive erosion and deposition. Plain Language Summary: Megafloods are catastrophic floods with a fast‐moving peak discharge of at least a million cubic meters (the volume of around 400 Olympic‐sized swimming pools) per second that are usually sourced from the sudden drainage of lakes formed behind unstable landslide or glacier dams. While previous scientists have studied the flow of megafloods in other, lower relief parts of the world, little is known about how these immense floods behave in steep mountainous landscapes. We simulated a megaflood in the eastern Himalaya and found that the simulated flood had a peak discharge of 3.1 million m 3 /s—three times higher than predicted from simple estimates using lake volume and dam height. We find that the hydraulics of this megaflood are directly related to the shape of the river valley (i.e., whether or not the water flowed over ridges and/or terraces or whether the river path took a sharp turn) and they change continuously throughout the flood. This means the patterns of removed material after a megaflood will be directly related to shape of the flooded landscape. Additionally, we predict that megafloods leave behind a lot of sand and large boulders—deposition that might impact where the modern river can erode. Key Points: 2D hydraulic simulation of a Holocene megaflood in the eastern Himalaya produces peak discharge of 3.1 × 10 6 m 3 /s and bed shear stress >100 kPa Local megaflood erosion will reflect interactions between valley topography and flood hydraulics more than patterns of unit stream power Megaflood boulder/sand deposits could impede later erosion by smaller flows with potential long‐term impacts on mountain landscape evolution